Evaluación de filtro percolador a escala piloto para la remoción de carga orgánica del efluente residual del centro de faenamiento, Calceta–Bolívar - Mendoza Ortega, Kelly Katherine (2021)
The research was aimed at evaluating a pilot-scale trickling filter for the removal of organic load from the residual effluent of the Calceta slaughterhouse. It was developed in three stages: 1) Characterize the residual effluent from the Calceta slaughterhouse; 2) Analyze the efficiency and technical-economic feasibility of the trickling filter in the removal of organic load from the slaughterhouse effluent. Quantitative methods were applied where flow measurements and quantitative analyses were used for parameters that indicate the quality of the pre and post treatment wastewater. In the characterization, an average flow of 9.15m3/day of wastewater was studied; days 5 and 12 (Friday) being the ones that generate a higher level of production. Most parameters, with the exception of pH (7.06), do not comply with the MSL, Table 8 of Ministerial Agreement 097-A. The treatment of waste water, through the percolator filter, determined a better quality and adjustment to the criteria of water quality contemplated in the Ecuadorian environmental regulations; in comparison with the initial levels. The trickling filter had a high efficiency in the removal of organic load (90.40% for COD and 79.40% for BOD). In addition, economically the costs to treat 1m3 of wastewater are low. It is accepted the idea to defend from the investigation; demonstrating that the trickling filter is technically and economically viable for the treatment of waste water coming from the Calceta slaughterhouse.